2023
DOI: 10.1158/2767-9764.crc-22-0278
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-derived GCSF Alters Tumor and Systemic Immune System Cell Subset Composition and Signaling

Abstract: While immunotherapies such as immune checkpoint blockade and adoptive T cell therapy improve survival for a subset of human malignancies, many patients fail to respond. Phagocytes including dendritic cells (DCs), monocytes (Mos), and macrophages (MFs) orchestrate innate and adaptive immune responses against tumors. However, tumor-derived factors may limit immunotherapy effectiveness by altering phagocyte signal transduction, development, and activity. Using Cytometry by Time-of-Flight (CyTOF) we found that tum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…Neutrophils to lymphocytes ratio has been suggested as a prognostic marker in many tumor patients, including ESCC (Kosumi et al, 2016; Templeton et al, 2014; Zhou et al, 2017). Neutrophils or MDSCs can functionally inactivate anti‐tumor immune cells, especially T cells, and induce immunosuppression (Coffelt et al, 2015; Gabrilovich & Nagaraj, 2009; Mantovani et al, 2011; Matos et al, 2023). It was observed that the expression level of iNOS was highly upregulated in the peripheral neutrophils from tumor‐bearing mice in a murine breast cancer model (Coffelt et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils to lymphocytes ratio has been suggested as a prognostic marker in many tumor patients, including ESCC (Kosumi et al, 2016; Templeton et al, 2014; Zhou et al, 2017). Neutrophils or MDSCs can functionally inactivate anti‐tumor immune cells, especially T cells, and induce immunosuppression (Coffelt et al, 2015; Gabrilovich & Nagaraj, 2009; Mantovani et al, 2011; Matos et al, 2023). It was observed that the expression level of iNOS was highly upregulated in the peripheral neutrophils from tumor‐bearing mice in a murine breast cancer model (Coffelt et al, 2015).…”
Section: Discussionmentioning
confidence: 99%